The use of language games to enhance the learning of vocabulary amongst year five students of SK Puruh Karu In Kuching / Richard Rait - Rait, Richard (2005)
This study was done to investigate iflanguage games could enhance learning of vocabulary among students of Sekolah Kebangsaan Puruh Karu. The research was conducted during normal lesson for six periods ofEnglish. The main focus ofthe research was teaching and learning vocabulary using games. Based on the data and the findings gathered from the study, it is obvious that games have positive effect on test scores. Playing while learning, students are able to recall what they have learned during the game. There is indication that there is some improvement in the students’ achievement after using games to learn vocabulary. The comparison in the mean scores for the groups, both the control and the experimental group in the post-test proves a positive result. Games are turnkey to enhance learning amongst students’ learning English language. Not only are games fun and entertaining but they can provide some options for teachers to get away from traditional learning methods.